Spatial integration and price transmission among major potato markets in India - Kumar, Rajeev R; Jha, Girish K; Choudhary, Kapil; Mishra, Dwijesh C (The Indian Journal of Agricultural Sciences, 2020)
The present study examined the spatial market integration across four major potato markets, viz. Agra, Bengaluru, Delhi and Mumbai for the period January, 2005–March, 2018. Johansen’s multivariate co-integration approach has been applied to identify the possible market integration. The results of Johansen’s co-integration test for different markets revealed that all the six market pairs are co-integrated, demonstrating that the selected potato markets have long-run price linkage across them. To supplement the finding of Johansen’s co-integration analysis, we assessed the nature and extent of long run and short run causal relationship between the markets. The results of long run causality showed bidirectional causality for the market pairs: Agra ↔ Bengaluru, Agra ↔ Mumbai, Bengaluru ↔ Delhi and Bengaluru ↔ Mumbai, whereas for market pairs Agra→ Delhi and Mumbai→ Delhi have long-run unidirectional causality. To get the additional evidence as to whether and in which direction price transmission is occurring between the market pairs in short run, Wald test has been used.